Mandarin-speaking children’s understanding of you ‘again’ with goal-PPs - Xu, Ting; Snyder, William; Christie, Stella (Proceedings of the Amsterdam Colloquium, 2022)
Like the adverb ‘again’ in many other languages, Mandarin you displays the repetitive/restitutive ambiguity when it modifies a goal-PP (e.g., ‘walk to the village’). This paper presents an experimental study which examined 4- and 5-year-old Mandarin-learning children’s comprehension of you with goal-PPs. The results show that children performed well on the repetitive and restitutive readings, supporting a structural account that would predict no delay in the acquisition of the restitutive reading.